Replication of putative susceptibility loci from genome-wide association studies associated with coronary atherosclerosis in Chinese Han population. - Fang Xie; Xun Chu; Hong Wu; Weiwei Sun; Min Shen; Lin Yang; Ying Wang; Yi Wang; Jinxiu Shi; Wei Huang (PLoS ONE, 2011)
BACKGROUND: Coronary atherosclerosis, the main cause of cardiovascular disease, is a progressive disease. Recent Genome Wide Association Studies (GWASs) discovered several novel loci associated with coronary artery disease (CAD) or its main complication myocardial infarction (MI). In this study, we investigated the associations between previously reported CAD- and MI-associated variants and coronary atherosclerosis in Chinese Han population. METHODOLOGY/PRINCIPAL FINDINGS: We performed a case-control association study with 2,335 coronary atherosclerosis patients and 1,078 controls undergoing coronary angiography of Chinese Han from China. Fourteen single nucleotide polymorphisms (SNPs), located at 1p13.3, 1q41, 2q36.3, 6q25.1, 9p21.3, 10q11.21 and 15q22.33, were genotyped in our sample collection. Six SNPs at 9p21 were associated with coronary atherosclerosis susceptibility (P(trend)<0.05) and rs10757274 showed the most significant association (P = 2.38×10(-08), OR = 1.34). These associations remained significant after adjustment for multiple comparisons. Rs17465637 at 1q41 (P(trend) = 6.83×10(-03), OR = 0.86) also showed significant association with coronary atherosclerosis, but the association was not significant after multiple comparisons. Additionally, rs501120 (P = 8.36×10(-03), OR = 0.80) at 10q11.21 was associated with coronary atherosclerosis in females, but did not show association in males and all participants. Variants at 1p13.3, 2q36.3, 6q25.1 and 15q22.33 showed no associations with coronary atherosclerosis and main cardiovascular risk factors in our data. CONCLUSIONS/SIGNIFICANCE: Our findings indicated variants at 9p21 were significantly associated with coronary atherosclerosis in Han Chinese. Variants at 1q41 showed suggestive evidence of association and variants at 10q11.21 showed suggestive evidence of association in females, which warrant further study in a larger sample.